Determination of Aflatoxin Level in Peanut and Reduction by Roasting - Arzandeh, Sahar (2010)
This study was conducted a) to validate the proper method for aflatoxin determination b) to determine aflatoxins in commercialized peanut in Selangor,Malaysia using High Performance Liquid Chromatography (HPLC) with fluorescence detector, and c) to determine the effects of oven roasting on aflatoxin reduction. Method validation for aflatoxins determination in peanut samples indicated a detection limit (LOD) of 0.01 ng/mL to 0.09 ng/mL and a quantification limit (LOQ) of 0.04 ng/mL to 0.3 ng/mL. The recovery for AFB1 ranged from 95.53% to 102.39%, AFB2 88.73% to 103.91%, AFG1 91.72% to 97.23%, and AFG2 74.85% to 78.00%. Eighty four samples of fresh shelled peanut were purchased from supermarkets in four locations (north, south, east and west regions) of Selangor state,Malaysia and aflatoxin level was determined using the validated method. The range of aflatoxin concentration was found to be from not detected to 97.28 ng/g in all samples investigated. About 78.57% of the samples were contaminated with aflatoxin. Moreover, 10.71% of the total samples exceeded the maximum tolerable limit of 15 ng/g set by the Codex and Malaysian Food Regulation. There was significant differences observed (p<0.05) in the aflatoxin levels among different supermarkets. To study the effect of oven roasting on aflatoxin reduction, naturally and artificially contaminated fresh shelled peanut samples were used. The effect of different levels of concentration (0 ng/g to 400 ng/g), temperature (90°C to 150°C)and time (30 to 120 min) were studied using CCD. The results indicated that oven roasting plays a significant role in aflatoxin reduction in peanut. There was not significant difference (p>0.05) in AFB1 reduction between artificially and naturally contaminated samples; however, there was a significant difference (p<0.05) in AFB2 reduction between artificially and naturally contaminated samples, with more reduction in naturally contaminated samples. Moreover, the level of aflatoxin reduction in artificially contaminated samples was more in the G series rather than in B counterparts (AFG2 and AFB1). The maximum AFB1, AFB2, AFG1, and AFG2 reduction in artificially contaminated peanut samples were 78.4%, 57.3%, 73.86% and 75.23%, respectively. Similarly the maximum AFB1 and AFB2 reduction in naturally contaminated peanut samples were obtained to be 80.17% and 69.73%,respectively.